2016
DOI: 10.1177/0033294116649144
|View full text |Cite
|
Sign up to set email alerts
|

Price Discrepancy Between Sellers and Buyers When Making Decisions for the Self and Others

Abstract: In daily life, people make decisions not only for themselves but also on behalf of others. There may be differences in terms of the endowment effect when making decisions in these two situations. In Study 1, this question was investigated with an existing dataset exploring the traditional endowment effect, in which 86 students (M age = 20.8 years, SD = 5.0) at Harvard University were asked to make a decision on selling or buying a coffee mug for themselves or for others as brokers. When making decisions for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Buyers with recent and recurring experiences in purchasing the service, however, may be more fluent with salient market dynamics and be less vulnerable to temporal effects. Prior CLT studies (e.g., Goodman and Malkoc 2012; Zhang, Zhang, and Li 2016) have focused on novel (e.g., new restaurants or online retailers) or isolated (e.g., buying ice cream on the way to a vacation) product choices and cases when consumers lack experience (e.g., selling coffee mugs to others), but our work confirms that recent experience reduces psychological distance effects (Benning, Breugelmans, and Dellaert 2012) for frequently repeated hedonic services. In line with Kyung, Menon, and Trope (2014), we suggest that future CLT work find other ways experience moderates psychological distance effects.…”
Section: Discussionsupporting
confidence: 72%
“…Buyers with recent and recurring experiences in purchasing the service, however, may be more fluent with salient market dynamics and be less vulnerable to temporal effects. Prior CLT studies (e.g., Goodman and Malkoc 2012; Zhang, Zhang, and Li 2016) have focused on novel (e.g., new restaurants or online retailers) or isolated (e.g., buying ice cream on the way to a vacation) product choices and cases when consumers lack experience (e.g., selling coffee mugs to others), but our work confirms that recent experience reduces psychological distance effects (Benning, Breugelmans, and Dellaert 2012) for frequently repeated hedonic services. In line with Kyung, Menon, and Trope (2014), we suggest that future CLT work find other ways experience moderates psychological distance effects.…”
Section: Discussionsupporting
confidence: 72%
“…Liu, Wang, Yao, Yang, & Wang, 2017; Polman, 2012b) and feel less fatigue after decision making (Polman & Vohs, 2016). In line with this, research has shown that the endowment effect, that is, sellers—as compared to buyers—ascribing more value to things merely because they own them, disappears when individuals made decisions for others in the role of brokers (Zhang, Zhang, & Li, 2016). Furthermore, individuals deciding for others (vs. themselves) are more willing to make changes from their current states of affair, which implies that they are less susceptible to the status quo effect (Lu & Xie, 2014).…”
mentioning
confidence: 91%